Hospitality and tourism education in an emerging digital economy. (20th March 2020) - Adeyinka-Ojo, Samuel; Lee, Sean; Abdullah, Shamsul Kamariah; Teo, John
Abstract : Purpose: This paper addresses the strategic industry challenge relating to new education frameworks. The paper identifies key digital literacy and employability skills that students and educators need to develop to better understand and negotiate the changing, digitally focused landscape of the hospitality and tourism industry (HTI). Design/methodology/approach: Content analysis was conducted on relevant literature related to digital technologies and employability skills. In particular, the paper explores the role of digital literacy and employability skills in an emerging digital economy and the disruptive impacts on hospitality and tourism operations. Findings: There are three key findings related to digital literacy skills and technologies: industry practitioner perspectives, employability skills and experience economy services and disruptive digital innovations. These findings are conceptualised to craft an innovative framework for technology-driven hospitality and tourism curriculum development. The framework developed in this paper will be of interest to both hospitality and tourism educators and managers in the increasingly digitalized Malaysian HTI. Originality/value: This paper presents an innovative, collaborative framework for hospitality and tourism curriculum development in education and industry to identify and develop the required digital literacy and employability skills.